2013
DOI: 10.3390/md11082927
|View full text |Cite
|
Sign up to set email alerts
|

Marinopyrrole Derivatives as Potential Antibiotic Agents against Methicillin-Resistant Staphylococcus aureus (II)

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) continues to be a major problem, causing severe and intractable infections worldwide. MRSA is resistant to all beta-lactam antibiotics, and alternative treatments are limited. A very limited number of new antibiotics have been discovered over the last half-century, novel agents for the treatment of MRSA infections are urgently needed. Marinopyrrole A was reported to show antibiotic activity against MRSA in 2008. After we reported the first total synthesis of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Gratifyingly, decreasing the catalyst loading to 5 mol% of Pd(OAc) 2 did not affect the yield. Replacing Pd(OAc) 2 with other palladium sources such as PdCl 2 , Pd 2 (dba) 3 and Pd(acac) 2 decreased the yield (entries [12][13][14]. Further screening of the reaction with respect to ligands revealed that phosphine ligands did not work under comparable conditions (entries 15-17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gratifyingly, decreasing the catalyst loading to 5 mol% of Pd(OAc) 2 did not affect the yield. Replacing Pd(OAc) 2 with other palladium sources such as PdCl 2 , Pd 2 (dba) 3 and Pd(acac) 2 decreased the yield (entries [12][13][14]. Further screening of the reaction with respect to ligands revealed that phosphine ligands did not work under comparable conditions (entries 15-17).…”
mentioning
confidence: 99%
“…[1] For instance, Tolmetin I, Zomepirac II and Ketorolac III as non-steroidal anti-inflammatory drugs (NSAID) have been shown to reduce hormones that cause pain and swelling, have antipyretic actions and are used as analgesics, respectively ( Figure 1). [2] Moreover, marinopyrrole derivatives IV are identified to display significant antibacterial activity against methicillin-resistant Staphylococcus aureus [3] and cytotoxicity against HCT-116 human colon cancer cells. [4] 2-Acylpyrroles are also versatile intermediates for the synthesis of alkaloids and other related heterocycles.…”
mentioning
confidence: 99%
“…Starting from our previously reported compound 2 [35], mono-ketone 4 was obtained in 73% yield over two steps by introduction of ortho- methoxy- para- methylphenyl group ( 3 was not isolated) followed by IBX oxidation (Scheme 1). Removal of TBDMS protecting group with TBAF gave alcohol 5 in 90% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Bisketone 8 was obtained in 54% yield after introduction of second ortho- methoxy- para- methylphenyl group (without isolation of 7 ) followed by IBX oxidation. Removal of para- toluenesulfonyl group with KOH generated 9 in 98% yield, which was converted to 10 in 65% yield by chlorination with NCS [35]. The final symmetrical marinopyrrole derivative 24 was obtained in 85% yield after demethylation using BBr 3 /DCM [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation